1988
DOI: 10.1164/ajrccm/138.2.350
|View full text |Cite
|
Sign up to set email alerts
|

Cause of the Raised Wedge Pressure on Exercise in Chronic Obstructive Pulmonary Disease

Abstract: Patients with chronic obstructive pulmonary disease (COPD) markedly increase their pulmonary artery wedge pressure on mild exercise even though they have no overt left heart disease and no increase in the esophageal pressure (as a reflection of mean intrathoracic pressure). We wondered if lung distension due to gas trapping during the hyperpnea of exercise might cause the wedge pressure to rise by increasing juxtacardiac pressures above esophageal pressures. If this were so, then (1) tachypnea alone, without e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
67
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 5 publications
1
67
0
2
Order By: Relevance
“…These findings are best explained by an incapacity of the heart to normally raise the cardiac output with exercise as its function is impaired by the pressure that surround it. Indeed, right heart catheterisation shows that patients with severe COPD who hyperinflate either during exercise or by voluntary hyperventilation develop high negative intra-thoracic pressures resulting in increased pulmonary and capillary wedge pressures, suggestive of left ventricular dysfunction [106]. Taken together these studies suggest that the function of the heart is mechanically constrained by the dynamic hyperinflation that is associated with exercise or increased ventilatory demand in patients with COPD whose resting hyperinflation is already a limiting problem.…”
Section: Cardiac Function During Exercisementioning
confidence: 98%
“…These findings are best explained by an incapacity of the heart to normally raise the cardiac output with exercise as its function is impaired by the pressure that surround it. Indeed, right heart catheterisation shows that patients with severe COPD who hyperinflate either during exercise or by voluntary hyperventilation develop high negative intra-thoracic pressures resulting in increased pulmonary and capillary wedge pressures, suggestive of left ventricular dysfunction [106]. Taken together these studies suggest that the function of the heart is mechanically constrained by the dynamic hyperinflation that is associated with exercise or increased ventilatory demand in patients with COPD whose resting hyperinflation is already a limiting problem.…”
Section: Cardiac Function During Exercisementioning
confidence: 98%
“…In the study of HILDE et al [6], PCWP was on average normal at rest, but increased markedly at exercise, in patients with, as well as without, pulmonary hypertension. It has been previously shown that in patients with COPD, PCWP and PAP increase at rest and more so at exercise, along with oesophageal pressures, in relation to dynamic hyperinflation and expiratory muscle contraction [14][15][16]. Therefore, pulmonary vascular pressures may actually increase with intrathoracic pressure becoming higher than reference atmospheric pressure, although a direct compression of the heart may also occur, thereby further increasing left ventricular end-diastolic pressure [14][15][16].…”
mentioning
confidence: 99%
“…It has been previously shown that in patients with COPD, PCWP and PAP increase at rest and more so at exercise, along with oesophageal pressures, in relation to dynamic hyperinflation and expiratory muscle contraction [14][15][16]. Therefore, pulmonary vascular pressures may actually increase with intrathoracic pressure becoming higher than reference atmospheric pressure, although a direct compression of the heart may also occur, thereby further increasing left ventricular end-diastolic pressure [14][15][16]. As illustrated in figure 1, intrathoracic pressure swings in patients with COPD may be huge, but are more positive than negative.…”
mentioning
confidence: 99%
See 2 more Smart Citations